The mythical golden age a critical discourse analysis of pro-Marcos historical negationism on TikTok - Ganancial, Kriza Jade P.; Glova, Nelfa M. (2023)
The Philippines is not only the social media capital but also the testing ground for a cat-and-mouse game of manipulation. This reality enabled the infiltration of pro-Marcos historical negationism in the initially entertaining and vulnerable TikTok platform particularly to weaponize discourses on the Marcosian mythical ?Golden Age?. Using a multimodal approach through social semiotics analysis, media ecology, theory of informed fiction, and basic concepts on democracy, this study examined discursive strategies in 10 disinformed TikTok videos, how the Marcoses are framed in these discourses, the role of the TikTok platform in reinforcing distortion, and its implications in democracy at large. It was revealed that pro-Marcos historical negationism capitalizes on the conjugal edifice complex, politicizes nostalgia, contradiction and evidentiality, us versus them dichotomizing mindset, referential nomination, victimization, whitewashing, dramatization, redemption arc, and argumentation. With that, the Marcoses are framed as strongmen, the messiah in the light-darkness-light perspective, and victims wronged by history. TikTok lubricates the spread of deceitful discourses and jeopardizes the digital wildfire of disinformation. Negationism disrupts the social symbolic meaning of discourse which favored the manipulation of signs and the competing of property and character information. Consequently, democracy is endangered by the insufficiency of the ?cures? to curb the systemic and historical problem.
Thesis (BA Communication and Media Arts) --University of the Philippines Mindanao, 2023